Genetic diversity of the Trypanosoma cruzi and Trypanosoma rangeli mini-exon gene in two localities of Southern Ecuador - Maiguashca Sánchez, Jalil (2018)
Trypanosoma cruzi, causative agent of Chagas Disease, and Trypanosoma 25 rangeli, are both protozoan parasites endemic to Latin America, including Ecuador. 26 T. cruzi shows high molecular and morphological heterogeneity and six lineages or 27 DTU’s are currently recognized. In Ecuador, TcI predominates while zymodeme III, 28 corresponding to what is currently TcIV, was previously reported by a single study. 29 T. rangeli, although nonpathogenic to humans, is a species of interest due to its 30 sympatric distribution with T. cruzi and confounding effect in Chagas Disease 31 diagnosis. In the present study, we isolated DNA of intestinal contents of triatomines 32 belonging to two communities of Southern Ecuador. Infection status determined by 33 kinetoplast-minicircle PCR was contrasted with results yielded by PCR amplification 34 of the non-transcribed region of the mini-exon gene. For disambiguation of the 35 results obtained, amplified fragments from the non-transcribed region of the mini-36 exon gene were sequenced using an Illumina MiSeq platform. We evaluated genetic 37 variability in terms of richness and diversity at a population level for both parasites 38 using Operational Taxonomic Units. T. cruzi genetic diversity was found to be 39 significantly larger in adult female vectors as compared to the nymphal stages. 40 Additionally, NGS revealed 21 mixed infections between TcI and T. rangeli, and the 41 presence of DTU TcIV in 7 samples, (a novel record in Southern Ecuador), which 42 the PCR-based methods were not able to detect. This suggests that the PCR-based 43 methods are not reliable as molecular tools for identification of mixed infections. 44 Furthermore, parasite populations present in only one of the two studied localities 45 were not found, suggesting active parasite dispersal over the study area. Our results highlight the value of NGS methodologies to clarify the population dynamics of 47 triatomines and inform control strategies.